Development of Validated Reversed-phase High-performance Liquid Chromatography Method for the Estimation of Nifedipine In situ Gel Form: Development of Validated Reversed-phase High-performance Liquid Chromatography Method for the Estimation of Nifedipine In situ Gel Form - Shelke, Ashwini (International Journal of Pharmaceutical & Biological Archive, 2019)
The primary point of this research was to develop the reversed-phase high-performance liquid chromatography (RP-HPLC) method for the determination of nifedipine in situ gel. The method development was done using different solvents, mobile phase composition, flow rate, and column. The developed technique was approved according to the ICH guideline Q2R1. Chromatographic separation of nifedipine from gel was achieved on Primesil C-8, dimension: 250 mm Ã— 4.6 mm, 5 Î¼, i.e. a stainless steel column 250 mm long, 4.6 mm id loaded with octadecyl silane chemically bonded to permeable silica particles of 5 Î¼m diameter maintained column oven temperature at 25Â°C. Acetonitrile:methanol:water in the ratio of 9:36:55 (v/v/v) was selected, as it gave symmetrical peak of nifedipine with minimal tailing. The chromatograph were recorded with UV vis detector at 235 nm wavelength and flow rate was 1 ml/min. The accuracy and precision of the methods were determined and validated statistically. Every method demonstrated great reproducibility and observed to be fast, exact, precise, and accurate with percent relative standard deviation <2. The method was observed to be simple, rapid, accurate, and precise. These methods can be effectively connected for the routine investigation of standard preparation and sample preparations.